Joint Power Allocation for Transmitter and Relay in a Full-Duplex Relay Covert Communication System - Gui Fang; Jin Chen; Guoxin Li; Rongrong He; Haichao Wang; Yang Yang (IEEE Open Journal of the Communications Society, 2024)
This paper considers a full-duplex relay-assisted system for covert communication, in which both the transmitter and the relay are the sender of covert messages. Different from current works that only consider the transmitter power optimization or relay power optimization individually, we propose a joint optimization approach for the transmitter and relay power, which is expected to enhance the system’s covert performance. We establish the minimum error detection probability using the Kullback-Leibler (KL) divergence, which serves as the foundation for formulating our joint optimization problem. The objective is to achieve the highest covert transmission rate within the constraints of covertness requirement and total power limitation. Employing a graphical method, we effectively transform inequality constraints into equality constraints, leading to the derivation of an optimal closed-form solution. The simulation results confirm the accuracy of the theoretical derivation and demonstrate that the proposed power allocation method is effective in determining the optimal power for both the transmitter and the full-duplex relay within a two-hop covert communication system.